Open Data as a key factor for developing expert systems: a perspective from Spain - Rodríguez Rojas, Luz Andrea; Cueva Lovelle, Juan Manuel; Tarazona Bermúdez, Giovanny Mauricio; Montenegro, Carlos Enrique (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2020)
The open data movement is relatively new but very significant, and potentially powerful. The overall intention is to make local, regional and national data available in a form that allows for direct manipulation. This paper is based on analyzing the current context of the Open Data initiative in Spain, from its origins and concepts, the legal framework, current initiatives and challenges that must be addressed for effective reuse of public sector information.
Keywords: open data; interoperability; linked data; egovernment; IJIMAI